EFFICACY OF SURGICAL TREATMENT FOR MECHANICAL JAUNDICE CAUSED BY CHRONIC DIFFUSE LIVER DISEASES - Азиатский международный университет (Web of Journals Publishing, 2024)
The aim of the study was to increase the effectiveness of surgical treatment for mechanical shock caused by chronic diffuse liver diseases.